Відповідь: 11
Пояснення:
[tex]a^n=\underbrace{a*a*\ldots*a*a} \\.\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ n[/tex]
(ab)^n = a^n * b^n
(a^n)^m = a^(nm)
(a/b)(c/d)=(ac)/(bd)
(a^n)/(a^m) = a^(n-m)
[tex]\frac{36^5}{2^9*3^8} =\\\\= \frac{(3*3*2*2)^5}{2^9*3^8} =\\\\=\frac{3^5*3^5*2^5*2^5}{2^9*3^8}=\\\\= \frac{3^{10}*2^{10}}{2^9*3^8} =\\\\=\frac{3^{10}}{3^8}*\frac{2^{10}}{2^9}=\\\\=3^2*2^1=(3*3)+(2)=9+2=11[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Відповідь: 11
Пояснення:
[tex]a^n=\underbrace{a*a*\ldots*a*a} \\.\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ n[/tex]
(ab)^n = a^n * b^n
(a^n)^m = a^(nm)
(a/b)(c/d)=(ac)/(bd)
(a^n)/(a^m) = a^(n-m)
[tex]\frac{36^5}{2^9*3^8} =\\\\= \frac{(3*3*2*2)^5}{2^9*3^8} =\\\\=\frac{3^5*3^5*2^5*2^5}{2^9*3^8}=\\\\= \frac{3^{10}*2^{10}}{2^9*3^8} =\\\\=\frac{3^{10}}{3^8}*\frac{2^{10}}{2^9}=\\\\=3^2*2^1=(3*3)+(2)=9+2=11[/tex]